A bismuth titanate composite photocatalyst and its preparation method and application
The preparation of Bi12TiO20/RGO composite photocatalysts by sol-gel method and hydrothermal method solves the problem of complex and high cost of the existing photocatalytic material preparation methods, achieves efficient photocatalytic degradation performance, and shows good stability in recycling.
Patent Information
- Application Number
- CN202111147569.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-09-29
AI Technical Summary
The existing preparation methods of photocatalytic materials are complex and costly, making it difficult to develop simple, environmentally friendly and efficient photocatalytic degradation materials.
Bi12TiO20/RGO composite photocatalyst was prepared by sol-gel method and hydrothermal method. The addition of graphene inhibited the agglomeration of Bi12TiO20 nanoparticles and increased the contact area between the catalyst and reactants.
The degradation performance of the photocatalyst on rhodamine B is improved, the degradation rate is significantly improved, and the composite photocatalyst shows good stability during recycling.
Smart Images

Figure CN113713801B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic degradation, and specifically relates to a bismuth titanate composite photocatalyst and a preparation method and application thereof. Background Art
[0002] Compared with adsorption, biodegradation and catalytic oxidation, the photocatalytic degradation method using sunlight has the advantages of low cost and low pollution. It is a green and environmentally friendly dye wastewater treatment method and has great application prospects in dye wastewater treatment. Currently, the most commonly used photocatalytic material is semiconductor material, among which wide-bandgap semiconductor materials have unique photoelectric properties and are therefore widely used in the field of photocatalysis.
[0003] The photocatalytic activity of bismuth titanate depends on its unique crystal structure and electronic structure. These crystal structures contain TiO6 octahedrons or TiO4 tetrahedrons. At the same time, the BiOn polyhedrons connected to TiO6 or TiO4 contain 6s2 lone pairs of electrons and Bi3+ with stereoactivity. These characteristics make bismuth titanate compounds have broad application prospects in the field of photocatalysis. In order to inhibit the agglomeration of nanoparticles and increase the stability of nanoparticles, people have designed different carriers (such as two-dimensional carbon materials and zeolites) to load semiconductor materials. However, these methods are relatively complex and costly, so it is necessary to develop a simple, environmentally friendly, and highly efficient composite material with photocatalytic degradation performance. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above and / or existing deficiencies in the prior art, the present invention provides a bismuth titanate composite photocatalyst and a preparation method and application thereof.
[0006] The present invention prepares Bi by sol-gel method and hydrothermal method 12 TiO 20 / RGO photocatalyst, in which the addition of graphene inhibits the Bi 12 TiO 20 The agglomeration of nanoparticles increases the contact area between the catalyst and the reactants, thus improving the performance of the photocatalyst for degradation of RhB.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a bismuth titanate composite photocatalyst, comprising:
[0008] Preparation of Bi by Sol-Gel Method 12 TiO 20 Gel, calcined to obtain Bi 12 TiO 20 Powder;
[0009] dissolving graphite oxide colloid and dispersing it to obtain graphene oxide dispersion;
[0010] Adding Bi to the graphene oxide dispersion 12 TiO 20 Powder, stirring, ultrasound, hydrothermal reaction;
[0011] After filtering, washing, drying and grinding, a bismuth titanate composite photocatalyst is obtained.
[0012] As a preferred embodiment of the method for preparing the bismuth titanate composite photocatalyst of the present invention, the sol-gel method is used to prepare Bi 12 TiO 20 Gel, dissolve bismuth salt in ethylene glycol, dissolve n-butyl titanate in hydrogen peroxide, add chelating agent to the two solutions, adjust pH with ammonia water, and get Bi in boiling water 12 TiO 20 gel.
[0013] As a preferred embodiment of the method for preparing the bismuth titanate composite photocatalyst of the present invention, the graphite oxide colloid is dissolved in distilled water to obtain a graphene oxide dispersion with a concentration of 2.11 g / L.
[0014] As a preferred solution of the method for preparing the bismuth titanate composite photocatalyst of the present invention, the dispersion is ultrasonic dispersion, the ultrasonic power is 250W, the ultrasonic time is 20 to 50min, and the ultrasonic frequency is 20 to 50kHz.
[0015] As a preferred embodiment of the method for preparing the bismuth titanate composite photocatalyst of the present invention, wherein: adding Bi to the graphene oxide dispersion 12 TiO 20 Powder, by mass ratio, Bi 12 TiO 20 The mass ratio of the powder to graphene oxide is 100:1-7.
[0016] As a preferred solution of the method for preparing the bismuth titanate composite photocatalyst of the present invention, the hydrothermal reaction has a reaction temperature of 120 to 180° C. and a reaction time of 12 to 18 hours.
[0017] As a preferred solution of the method for preparing the bismuth titanate composite photocatalyst of the present invention, the drying is vacuum drying, the drying temperature is 60° C. to 80° C., and the drying time is 12 h to 24 h.
[0018] Another object of the present invention is to provide a bismuth titanate composite photocatalyst obtained by the preparation method as described above.
[0019] Another object of the present invention is to provide the use of the bismuth titanate composite photocatalyst as described above in the degradation of rhodamine B.
[0020] As a preferred solution for the application of the bismuth titanate composite photocatalyst of the present invention in the degradation of rhodamine B, the concentration of rhodamine B is lower than 20 mg / L.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] Preparation of Bi by sol-gel method and hydrothermal method 12 TiO 20 / RGO photocatalyst, in which the addition of graphene inhibits the Bi 12 TiO 20 The agglomeration of nanoparticles increases the contact area between the catalyst and the reactants, accelerates the transfer of photogenerated carriers, and avoids their recombination, thereby improving the performance of the photocatalyst in degrading rhodamine B. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0024] Figure 1 Bi prepared in Examples 1 and 3 12 TiO 20 XRD pattern of / RGO photocatalyst.
[0025] Figure 2 Bi prepared in Example 3 12 TiO 20 TEM image of / RGO photocatalyst.
[0026] Figure 3 Bi prepared in Example 3 12 TiO 20 / The effect diagram of the recycling of RGO photocatalyst.
[0027] Figure 4 Bi with different loading amounts of graphene prepared in Examples 1 and 5 12 TiO 20 / RGO photocatalyst catalytic degradation of Rhodamine B control experimental effect diagram.
[0028] Figure 5 Bi prepared in Example 3 12 TiO 20 Degradation diagram of Rhodamine B at different concentrations by RGO / RGO photocatalyst. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0032] Example 1
[0033] (1) Weigh 2.90 g of Bi(NO3)3〃5H2O and dissolve it completely in 30 mL of ethylene glycol under stirring to make it evenly dispersed;
[0034] (2) Weigh 0.17 g of n-butyl titanate and dissolve it in 5 mL of 30% hydrogen peroxide solution to make it evenly dispersed;
[0035] (3) Weigh 4.20 g of citric acid as a chelating agent and add it to the two solutions, and adjust the pH of the two solutions to 9 with ammonia water;
[0036] (4) The two solutions were mixed together, stirred for 1 hour, and the resulting suspension was heated in a boiling water bath to obtain Bi 12 TiO 20 gel;
[0037] (5) Obtained Bi 12 TiO 20 The gel was dried in a blast drying oven at 140°C to form a fluffy precursor. The precursor was placed in a tube furnace and heated to 550°C at a rate of 2°C / min. It was calcined for 1h to obtain a light yellow Bi 12 TiO 20 ;
[0038] The prepared Bi was tested by degrading Rhodamine B under simulated sunlight irradiation. 12 TiO 20 The catalytic activity of the catalyst was good. When used to degrade Rhodamine B, the reaction conditions were: 40 mL of 20 mg / L Rhodamine B aqueous solution, 10 mg of catalyst, firstly, the absorption equilibrium was established in the dark, and then the light was turned on for photocatalytic reaction. It was found that the degradation rate of Rhodamine B was 75% in 210 minutes.
[0039] Example 2
[0040] (1) Weighing 0.097 g (solid content 2.11%) of graphite oxide in 30 mL of deionized water, ultrasonically dispersing it at a frequency of 50 kHz for 30 min to obtain a graphene oxide dispersion;
[0041] (2) Weigh 0.20 g of Bi obtained by calcination in Example 1. 12 TiO 20 Add into the graphene oxide dispersion which has been uniformly dispersed by ultrasound, stir for 3 hours, and then ultrasonicate for 1 hour at a frequency of 50 kHz;
[0042] (3) placing the mixed solution in a stainless steel autoclave lined with polytetrafluoroethylene and reacting at 120° C. for 12 h;
[0043] (4) The solid was filtered off and washed with distilled water and alcohol for several times, and dried at 80°C for 8 h to obtain a bismuth titanate composite photocatalyst, which was labeled as Bi 12 TiO 20 / RGO1 composite photocatalyst;
[0044] The prepared Bi was tested by degrading Rhodamine B under simulated sunlight irradiation. 12 TiO 20 / RGO1 photocatalyst catalytic activity. When used to degrade rhodamine B, the reaction conditions were: 40 mL of 20 mg / L rhodamine B aqueous solution, 10 mg of catalyst, firstly establish absorption equilibrium under dark conditions, then turn on the light for photocatalytic reaction, and it was found that the degradation rate of rhodamine B was 76% in 210 min.
[0045] Example 3
[0046] (1) Weighing 0.29 g (solid content 2.11%) of graphite oxide in 30 mL of deionized water, ultrasonically dispersing it at a frequency of 50 kHz for 30 min to obtain a graphene oxide dispersion;
[0047] (2) Weigh 0.20 g of Bi obtained by calcination in Example 1. 12 TiO 20Add into the graphene oxide dispersion which has been uniformly dispersed by ultrasound, stir for 3 hours, and then ultrasonicate for 1 hour at a frequency of 50 kHz;
[0048] (3) placing the mixed solution in a stainless steel autoclave lined with polytetrafluoroethylene and reacting at 120° C. for 12 h;
[0049] (4) The solid was filtered off and washed with distilled water and alcohol for several times, and dried at 80°C for 8 h to obtain a bismuth titanate composite photocatalyst, which was labeled as Bi 12 TiO 20 / RGO3 composite photocatalyst;
[0050] The prepared Bi was tested by degrading Rhodamine B under simulated sunlight irradiation. 12 TiO 20 / RGO3 photocatalyst catalytic activity. When used to degrade rhodamine B, the reaction conditions were: 40 mL of 20 mg / L rhodamine B aqueous solution, 10 mg of catalyst, first establish absorption equilibrium under dark conditions, then turn on the light for photocatalytic reaction, and it was found that the degradation rate of rhodamine B was 98% in 210 min.
[0051] Bi 12 TiO 20 The experimental results of using the / RGO3 composite photocatalyst for 5 cycles to degrade RhB are shown in Table 1. It can be seen from Table 1 that Bi 12 TiO 20 After the / RGO3 composite photocatalyst was recycled for 5 times, Bi 12 TiO 20 The degradation rate of Rhodamine B over / RGO3 photocatalyst was still as high as 88.5% within 210 min.
[0052] Table 1
[0053]
[0054] Figure 1 Bi prepared in Examples 1 and 3 12 TiO 20 and Bi 12 TiO 20 XRD patterns of / RGO3 catalyst, Bi 12 TiO 20 / RGO3andBi 12 TiO 20 All peaks correspond to the cubic phase structure Bi 12 TiO 20 Crystal plane (JCPDS No.34-0097), and the characteristic diffraction peak is sharp, and no impurity peak appears, indicating that Bi 12 TiO 20The sample has good crystallinity and high purity. Bi prepared by combining with graphene 12 TiO 20 / RGO3 crystal surface and Bi 12 TiO 20 The crystal planes corresponded completely, and the RGO sheets were successfully peeled off.
[0055] Example 4
[0056] (1) Weighing 0.48 g (solid content 2.11%) of graphite oxide in 30 mL of deionized water, ultrasonically dispersing it at a frequency of 50 kHz for 30 min to obtain a graphene oxide dispersion;
[0057] (2) Weigh 0.20 g of Bi obtained by calcination in Example 1. 12 TiO 20 Add into the graphene oxide dispersion which has been uniformly dispersed by ultrasound, stir for 3 hours, and then ultrasonicate for 1 hour at a frequency of 50 kHz;
[0058] (3) placing the mixed solution in a stainless steel autoclave lined with polytetrafluoroethylene and reacting at 120° C. for 12 h;
[0059] (4) The solid was filtered off and washed with distilled water and alcohol for several times, and dried at 80°C for 8 h to obtain a bismuth titanate composite photocatalyst, which was labeled as Bi 12 TiO 20 / RGO5 composite photocatalyst;
[0060] The prepared Bi was tested by degrading Rhodamine B under simulated sunlight irradiation. 12 TiO 20 / RGO5 photocatalyst catalytic activity. When used to degrade rhodamine B, the reaction conditions were: 40 mL of 20 mg / L rhodamine B aqueous solution, 10 mg of catalyst, firstly establish absorption equilibrium under dark conditions, then turn on the light for photocatalytic reaction, and it was found that the degradation rate of rhodamine B was 81% in 210 min.
[0061] Example 5
[0062] (1) Weighing 0.68 g (solid content 2.11%) of graphite oxide in 30 mL of deionized water, ultrasonically dispersing it at a frequency of 50 kHz for 30 min to obtain a graphene oxide dispersion;
[0063] (2) Weigh 0.20 g of Bi obtained by calcination in Example 1. 12 TiO 20 Add into the graphene oxide dispersion which has been uniformly dispersed by ultrasound, stir for 3 hours, and then ultrasonicate for 1 hour at a frequency of 50 kHz;
[0064] (3) placing the mixed solution in a stainless steel autoclave lined with polytetrafluoroethylene and reacting at 120° C. for 12 h;
[0065] (4) The solid was filtered off and washed with distilled water and alcohol for several times, and dried at 80°C for 8 h to obtain a bismuth titanate composite photocatalyst, which was labeled as Bi 12 TiO 20 / RGO7 composite photocatalyst;
[0066] The prepared Bi was tested by degrading Rhodamine B under simulated sunlight irradiation. 12 TiO 20 / RGO1 photocatalyst catalytic activity. When used to degrade rhodamine B, the reaction conditions were: 40 mL of 20 mg / L rhodamine B aqueous solution, 10 mg of catalyst, firstly establish absorption equilibrium under dark conditions, then turn on the light for photocatalytic reaction, and it was found that the degradation rate of rhodamine B was 87% in 210 min.
[0067] Figure 3 Bi with different graphene loadings obtained in Examples 1 to 5 12 TiO 20 The catalytic degradation diagram of Rhodamine B by / RGO photocatalyst. Figure 3 It can be seen that compared with Bi 12 TiO 20 ,Bi 12 TiO 20 The degradation rate of RhB increased by 22% with the increase of RGO content. The degradation of RhB first increased and then decreased. This is because the two-dimensional sheet structure and large specific surface area of graphene inhibit the agglomeration of nanoparticles, making Bi 12 TiO 20 Nanoparticles have smaller particle size and better dispersibility, which increases the contact area between the catalyst and the reactant, thus showing excellent catalytic activity during the reaction and being more conducive to the photocatalytic degradation of RhB. However, as the graphene content increases further, the Bi 12 TiO 20 The number further decreases, resulting in a decrease in the catalytic performance of the composite.
[0068] Example 6
[0069] This Example 6 is basically the same as Example 3, except that the reaction temperature in step (3) is different, and the catalytic activity of the prepared photocatalyst is tested by degrading rhodamine B under simulated sunlight. When used to degrade rhodamine B, the reaction conditions are: 40 mL of a 20 mg / L rhodamine B aqueous solution, 10 mg of a catalyst, first establishing absorption equilibrium under dark conditions, and then turning on the light for photocatalytic reaction. The test results are shown in Table 2.
[0070] Table 2
[0071] Reaction temperature Degradation rate of Rhodamine B at 210 min 120℃ 98% 140℃ 80% 160℃ 70% 180℃ 70%
[0072] It can be seen from the data in Table 2 that the Bi prepared at different hydrothermal temperatures 12 TiO 20 The photocatalytic performance of / RGO3, Bi prepared at a hydrothermal temperature of 120℃ 12 TiO 20 / RGO3 has the best photocatalytic performance, and it can be concluded that 120℃ is the optimal experimental temperature.
[0073] Example 7
[0074] The Bi prepared in Example 3 was tested under simulated sunlight. 12 TiO 20 The catalytic activity of the / RGO3 composite photocatalyst in degrading different concentrations of Rhodamine B. The reaction conditions for degrading different concentrations of Rhodamine B were: 40 mL of Rhodamine B aqueous solution with concentrations of 10, 20, 30 and 40 mg / L, and 10 mg of catalyst. The absorption equilibrium was first established in the dark, and then the light was turned on for photocatalytic reaction. The test results are shown in Figure 4 shown.
[0075] Figure 4 for Bi 12 TiO 20 / Experimental results of RGO3 degradation of different concentrations of Rhodamine B, such as Figure 4 As shown in Figure 2, when the initial concentration of RhB was lower than 20 mg / L, RhB was replaced by Bi within 3 h. 12 TiO 20 / RGO is completely degraded. When the initial concentration of RhB is 40 mg / L, Bi 12 TiO 20 The degradation rate of RhB by / RGO dropped to about 60%. This is mainly because: (1) the surface active sites of the photocatalyst are fixed and can only degrade a certain concentration of RhB solution within a certain range; (2) excessive RhB is deposited on the catalyst surface, resulting in catalyst deactivation.
[0076] Preparation of Bi by sol-gel method and hydrothermal method12 TiO 20 / RGO photocatalyst, in which the addition of graphene inhibits the Bi 12 TiO 20 The agglomeration of nanoparticles increases the contact area between the catalyst and the reactants, accelerates the transfer of photogenerated carriers, and avoids their recombination, thereby improving the performance of the photocatalyst in degrading rhodamine B.
[0077] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. Application of a bismuth titanate composite photocatalyst in the degradation of rhodamine B at a concentration of 20 mg / L, characterized in that: The reaction conditions for degradation of Rhodamine B are: 40 mL of 20 mg / L Rhodamine B aqueous solution and 10 mg of catalyst under simulated sunlight, first establish absorption equilibrium in the dark, then turn on the light for photocatalytic reaction, and the degradation rate of Rhodamine B is 98% in 210 minutes; The method for preparing the bismuth titanate composite photocatalyst comprises: 2.90 g Bi(NO3)3·5H2O was weighed and completely dissolved in 30 mL ethylene glycol under stirring to make it uniformly dispersed; 0.17 g n-butyl titanate was weighed and dissolved in 5 mL 30% hydrogen peroxide solution to make it uniformly dispersed; 4.20 g citric acid was weighed and added to the two solutions as a chelating agent, and the pH of the above two solutions was adjusted to 9 with ammonia water; the two solutions were mixed together, stirred for 1 h, and the resulting suspension was heated in a boiling water bath to obtain Bi 12 TiO 20 Gel; obtained Bi 12 TiO 20 The gel was dried in a forced air drying oven at 140 °C to form a fluffy precursor. The precursor was placed in a tube furnace and heated to 550 °C at a rate of 2 °C / min and calcined for 1 h to obtain a light yellow Bi 12 TiO 20 ; Weigh 0.29 g of graphite oxide with a solid content of 2.11% in 30 mL of deionized water, and ultrasonicate at a frequency of 50 kHz for 30 min to disperse it evenly to obtain a graphene oxide dispersion. Weigh 0.20 g of the calcined Bi 12 TiO 20 The mixture was added into the graphene oxide dispersion which had been uniformly dispersed by ultrasound, stirred for 3 h, and then ultrasonicated for 1 h at a frequency of 50 kHz. The mixed solution was placed in a stainless steel high-pressure reactor lined with polytetrafluoroethylene and reacted at 120 °C for 12 h. The solid was filtered out and washed with distilled water and alcohol for several times, and dried at 80 °C for 8 h to obtain a bismuth titanate composite photocatalyst.
Citation Information
Patent Citations
Preparation method of graphene / bismuth titanate photocatalytic material
CN104353449A
Method for preparing Bi2Ti2O7-TiO2 / RGO nanocomposite material with visible-light response
CN110787792A